2007
DOI: 10.1063/1.2756832
|View full text |Cite
|
Sign up to set email alerts
|

Tight-binding molecular dynamics study of the role of defects on carbon nanotube moduli and failure

Abstract: We performed tight-binding molecular dynamics on single-walled carbon nanotubes with and without a variety of defects to study their effect on the nanotube modulus and failure through bond rupture. For a pristine (5,5) nanotube, Young's modulus was calculated to be approximately 1.1 TPa, and brittle rupture occurred at a strain of 17% under quasistatic loading. The predicted modulus is consistent with values from experimentally derived thermal vibration and pull test measurements. The defects studied consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 38 publications
6
22
0
Order By: Relevance
“…Moreover, the laser process leads to CNTs of the highest purity and quality (few defects, high crystallinity, low amorphous carbon content) and larger aspect ratio (>10 000) when compared with any other synthesis methods; these characteristics make them potentially more efficient for composite reinforcement [49]. Acid treatments, such as that used in this work to purify the arc grown SWCNTs, are known to shorten the CNTs and induce defects on their side walls, thus having detrimental effects on mechanical properties of the SWCNTs [50]. However, further experiments would be required to confirm the reasons for the differences observed among the composites tested.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…Moreover, the laser process leads to CNTs of the highest purity and quality (few defects, high crystallinity, low amorphous carbon content) and larger aspect ratio (>10 000) when compared with any other synthesis methods; these characteristics make them potentially more efficient for composite reinforcement [49]. Acid treatments, such as that used in this work to purify the arc grown SWCNTs, are known to shorten the CNTs and induce defects on their side walls, thus having detrimental effects on mechanical properties of the SWCNTs [50]. However, further experiments would be required to confirm the reasons for the differences observed among the composites tested.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…This is not surprising since the purity, quality, aspect ratio and nature of impurities, hence the source of SWCNTs are determining factors in the final properties of CNT based composites. It has recently been shown that defects have detrimental effects on mechanical properties of SWCNTs [49]. The laser process produces CNTs of the highest quality (few defects, high crystallinity) as compared to any other synthesis methods known; it also generates nanotubes with very large aspect ratio (>10,000).…”
Section: Mat (% Swcnts)mentioning
confidence: 99%
“…They took pristine as well as defective CNTs with one and two atom vacancies. The role of defects on carbon nanotube elastic moduli and failure behavior was studied by tight binding molecular dynamics simulation by Haskins et al (Haskins et al, 2007). Molecular simulation was used by Yang et al (Yang et al, 2007) to determine the fracture strength of single-wall carbon nanotubes containing different concentrations of randomly distributed point defects.…”
Section: Theoretical Predictions and Experimental Observationsmentioning
confidence: 99%